Hubungan Dinamika Sosial Ekonomi Wilayah dengan Interaksi Ruang Kawasan Perbatasan di Pulau Sebatik, Kalimantan Utara - Agung Satriyo Nugroho; Rijanta; Santoso, Purwo; Marfai, Muh Aris (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The state border area has an important position for state sovereignty. Sebatik Island is one of the border areas designated as PKSN for defense and security purposes, along with a new growth center in the economic sector. Therefore it is necessary to know the development of the socio-economic condition of the region along with the various spatial interaction activities that have been carried out by the border communities of Sebatik Island. This paper aims to (1) identify the socio-economic conditions of the area in the Sebatik Island Border Area, (2) identify spatial interaction activities carried out by border communities on Sebatik Island in order to fulfill their daily needs, (3) assess the relationship between socio-economic conditions in ​​Sebatik Island with spatial interactions between regions that have been carried out by the community. This study uses qualitative methods by applying the principle of data triangulation. Some research results can be fund is the Sebatik island region still has a dependence on other regions, one of which is on the territory of neighboring countries. This becomes an anomaly if it is associated with the function of the border area as a manifestation of state sovereignty